The significance of public space in assessing architectural heritage - Coll-Pla, Sergio; Medina-Sánchez, Tatiana; Cuzziramos-Gutiérrez, Fernando; Mayta-Ponce, Denis L.; Málaga-Montoya, Daniel; Costa-Jover, Agustí; Mallafrè-Balsells, Cèlia (Journal of Architecture and Urbanism, 2024)
This study examines the relationship between public spaces surrounding heritage buildings in Arequipa, Peru, and social perceptions of these structures. Focusing on buildings recognized as significant architectural landmarks by the magazine “El arquitecto Peruano” founded by Belaunde Terry. The research reveals a weak correlation between the quality of the surrounding public space and the society’s appreciation of the architectural edifice. However, certain buildings stand out in public esteem, notably Plaza de Armas, Convento de Santa Catalina, Iglesia de la Compañía, Templo de Yanahuara, Iglesia de San Agustín, and Iglesia de Cayma, primarily due to their Ba-roque-mestizo architectural style. The text emphasizes the pivotal role of public spaces in the evaluation of architectural heritage. This research sheds light on the complex interplay between architectural heritage, public spaces, and social perception, offering valuable insights for urban planning and heritage preservation initiatives.